Flocking Behavior of Boids Driven by Hyperchaotic MACM System - Rosa Martha López-gutiérrez; Lılıana Cardoza Avendaño; Ana Medina; Cesar Cruz Hernández (Chaos Theory and Applications)
In the present work a detailed study is presented, on the design, programming, and investigation of the behavior of flocking (Movement type flock), through the model of BOIDS, for its acronym in English "Bird Oid Object" (Object type bird), which was devised by Craig Reynolds in 1986. This complex flocking behavior that occurs arises from the interaction of simple local rules, in which complexity and sensitivity to initial conditions are present. A measure of chaotic compound will be introduced to the algorithm by means of a new four-dimensional autonomous hyperchaotic system based on the 3D Méndez-Arellano-Cruz-Martínez (MACM) system. The measures proposed herein, therefore, may have the potential to predict, control, and exemplify the behavior of group intelligence study systems that occur in nature, allowing the implementation of these systems in groups of robots through the implementation of hyperchaotic trajectories in the future, to obtain greater speed and efficiency, obstacle and collisions avoidance in their flights.